Determinants of the Level of Stock Underpricing When a Company Makes an Initial Public Offering on the Indonesian Stock Exchange in the 2021-2024 Period - Kartika, Indri; Yuliana, Indah; Indriastuti, Maya; Najihah, Naila (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Underpricing, which refers to the difference between the Initial Public Offering (IPO) price and the closing price on the first trading day, can lead to financial disadvantages for issuers by offering shares below their actual value. This research explores the factors influencing underpricing, including the reputations of underwriters and auditors, financial indicators such as the Debt-to-Equity Ratio (DER) and Earnings Per Share (EPS), firm-specific characteristics like company size and age, as well as profitability as indicated by Return on Equity (ROE). The study analyzed data from 161 companies that launched IPOs on the Indonesia Stock Exchange during the 2021–2024 period, selected through purposive sampling. To assess the impact of these variables on underpricing, a multiple linear regression approach was utilized. The findings indicate that larger firm size, older firm age, higher EPS and ROE, along with reputable auditors, significantly lower the level of underpricing. In contrast, a higher DER contributes to greater underpricing. Meanwhile, underwriter reputation, though positively related, does not exhibit a statistically significant impact. The study acknowledges limitations in the exclusion of industry sector differentiation and reliance on historical data, which may limit the findings’ generalizability. Future research should consider more advanced econometric methods and incorporate additional variables. These findings suggest that investors should prioritize fundamental financial and governance factors over potential short-term gains from underpricing when evaluating IPOs.